Edukasi Pembuatan Muniman Herbal Penurun Hipertensi Berbahan Bunga Telang (Clitoria Ternatea) pada Masyarakat Dusun 1 Desa Bahagia Kecamatan Palolo - Arniawan, Arniawan; Kandita, Mila; Versha, Versha; Aulia A, Nasywa; Gracella, Laura; Marifa, Marifa; Adelia, Sasrina; Sakariya, Sakariya; Ramadan, Andra; Billy, Alfrian; Dinar, Syam (Civiliza Publishing, 2024)
Hypertension is a condition where blood pressure in the blood vessels increases chronically and is still a serious health problem because its arrival is often not noticed and can continue to get worse until it reaches a level that threatens the life of the sufferer. Therefore, therapy is needed to overcome hypertension, namely with non-pharmacological therapy, one of the treatments for hypertension using non-pharmacology can use butterfly pea flowers (clitoria ternatea). The purpose of this community service is to educate the community about making herbal drinks to lower hypertension from butterfly pea flowers (clitoria ternatea). With the method of socialization and discussion and evaluated to assess the level of knowledge through pre-test and post-test questionnaires. From 15 people in Hamlet I, Bahagia Village, a pre-test was obtained with level of knowledgethe less category with a total of 8 people (54.4%), the sufficient category with 5 people (33.3%) and the good category with 2 people (13.3%) Meanwhile, the post-test results showed that the level of knowledge was in the poor category with 1 person (6.7%), the sufficient category was 2 people (13.3%) and the good category was 12 people (80%). From the comparison of the results, there is an increase in public knowledge and understanding of the material provided. This activity can be carried out well thanks to cooperation. The Head of Bahagia Village, the Midwife of Bahagia Village, the Head of Hamlet I and local residents who have a history of hypertension willing to be a participant.